The Safety of Hyperbaric Oxygen Therapy in the Treatment of Covid-19 - O. A. Levina; A. K. Еvseev; A. K. Shabanov; V. V. Kulabukhov; N. Y. Kutrovskaya; I. V. Goroncharovskaya; K. A. Popugaev; D. A. Kosolapov; D. S. Slobodeniuk; S. S. Petrikov (Неотложная медицинская помощь, 2020)
Relevance. Acute respiratory infection COVID-19 caused by the SARS-CoV-2 (2019-nCov) coronavirus is severe and extremely severe in 15—20% of cases, which is accompanied by the need for respiratory support. Hyperbaric oxygenation is recognized as an effective therapy for replenishing any form of oxygen debt.Aim of study. To study the safety of HBO use in patients with COVID-19.Material and metods. We examined 32 patients with the diagnosis “Coronavirus infection caused by the virus SARS-CoV-2” (10 — moderately severe patients (CT 1–2), 22 — patients in serious condition (CT 3–4), who received course of hyperbaric oxygenation (HBO). The procedures were carried out in a Sechrist 2800 chamber (USA) at a mode of 1.4–1.6 AT for no more than 60 minutes. In total, the patients received 141 HBO sessions. Before and after each HBO session, the subjective indicators of the patient’s condition were assessed and the blood oxygen saturation was measured.Results. An algorithm for HBO course management was developed, which consists in using “soft” modes (up to 1.4 AT) during the first session, followed by pressure adjustment (not higher than 1.6 AT) during the course to achieve maximum therapeutic effect and comfort for the patient. Against the background of the HBO course, the patients showed an increase in blood oxygen saturation in patients in both surveyed groups, as well as positive dynamics in the form of a decrease in shortness of breath, an improvement in general well-being.Conclusion. The inclusion of daily sessions (at least 4) of hyperbaric oxygenation in “soft” modes (1.4–1.6 ATA) in the complex therapy for COVID-19 has shown its safety and preliminary positive effect on the subjective state of the examined patients and the dynamics of blood oxygen saturation.